2018
DOI: 10.1590/1678-98652018000600002
|View full text |Cite
|
Sign up to set email alerts
|

Excessive abdominal adiposity and body fat are associated with lower serum vitamin D levels: A population-based study

Abstract: Objective To estimate the prevalence of 25-hydroxyvitamin D deficiency and to analyze factors associated with lower serum vitamin levels in Brazilian adults. Methods A cross-sectional, population-based study consisted of 626 adult individuals of both sexes living in the urban area of Viçosa, Minas Gerais. The dependent variable used was the serum level of 25-hydroxyvitamin D and the independent variables were sociodemographic, anthropometric and body composition variables. The associations among the variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In this study, vitamin D deficiency was more common in women. Some studies are compatible with our results, and some studies do not support them [33][34][35][36]. The high prevalence of vitamin D deficiency in women may be related to many factors such as the style of clothing, age, sunbathing time, skin color, etc.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, vitamin D deficiency was more common in women. Some studies are compatible with our results, and some studies do not support them [33][34][35][36]. The high prevalence of vitamin D deficiency in women may be related to many factors such as the style of clothing, age, sunbathing time, skin color, etc.…”
Section: Discussionsupporting
confidence: 47%
“…There are studies that indicate that the consumption of high-energy foods, although unhealthy, can lead to a change in body composition, such as an increase in the BMI, which would imply good bone health, as excessive body mass increases the mechanical load, which in turn activates bone metabolism [42,44]. In contrast, some studies have indicated that excess body and abdominal adiposity are strong predictors of low vitamin D levels in the blood, a fundamental agent of bone metabolism [45,46]. Additionally, there is evidence that there are receptors in adipose tissue that cause the retention of this vitamin [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical and practical training for data collection was carried out, in addition to a pilot study with eighty-four individuals, aiming to identify possible errors in the elaboration and application of the questionnaire, as well as in the protocols for anthropometric measurements and biochemical tests. Further details about the study protocol were previously described (8) .…”
Section: Study Design and Participantsmentioning
confidence: 99%